The Methods On Diagnostics Of The Reflexive Abilities At Future Teachers-Psychologists - Irina Rovnyakova, Irina Stebletsova, Karas Kaziyev, Saniya Nurgaliyeva, Kadisha Shalgynbayeva, (Opción, 2019)
The article is devoted to the research of the main methods of diagnostics of reflexive abilities at future teachers-psychologists in the training process at a higher education institution via comparative qualitative research methods. As a result, before diagnosing and developing reflexive abilities at students, it is necessary to study the level of readiness for the development of these abilities, to prepare them for reflexive activity. In conclusion, each researcher chooses which methods to use for diagnostics, depending on his views, principles, tasks and purposes